2021
DOI: 10.2147/cmar.s281377
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0005927 Inhibits the Progression of Colorectal Cancer by Regulating miR-942-5p/BATF2 Axis

Abstract: Background Colorectal cancer (CRC) is one of the most common aggressive neoplasms worldwide. Circular RNAs (circRNAs) have been involved in the biological process of CRC. This study aimed to explore the effects of circ_0005927 on CRC progression and underneath mechanism. Materials and Methods The expression of circ_0005927, microRNA-942-5p (miR-942-5p) and basic leucine zipper ATF-like transcription factor 2 (BATF2) was detected by quantitative real time polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…circ_0002162 promotes the malignant development of tongue cancer ( Zhang et al, 2021a ). Additionally, the overexpression of circ_0005927 restrains the development of colorectal carcinoma ( Yu et al, 2021b ). Moreover, circ_0015326 facilitates the invasion, migration, and proliferation of ovarian cancer ( Zhang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…circ_0002162 promotes the malignant development of tongue cancer ( Zhang et al, 2021a ). Additionally, the overexpression of circ_0005927 restrains the development of colorectal carcinoma ( Yu et al, 2021b ). Moreover, circ_0015326 facilitates the invasion, migration, and proliferation of ovarian cancer ( Zhang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been initially indicated that circRNAs could mediate miRNA functions (e.g., via sponging) and control important events in transcription (e.g., RNA folding and endonuclease protection) [19]. In addition, it has been demonstrated in current evidence that circRNAs contain multiple microRNA response elements (MREs) that can bind to miRNAs, commonly called "miRNA sponges," which could relieve the targeted inhibition of downstream mRNAs by miRNAs [29][30][31]. In this study, the underlying molecular mechanisms of AAAs have been investigated based on ceRNA regulatory hypothesis of circRNAs, miRNA, and mRNA.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Therefore, subsequent studies, including ours, mainly focused on gene expression regulation through exploring the upstream transcriptional factors, microRNAs, circular RNAs and N6‐methyladenosine modification of BATF2. 12 , 14 , 15 , 17 , 18 , 19 , 20 Our previous work also identified a transcriptional factor, glucocorticoid receptor, which could induce BATF2 expression in lymphoma cells. 12 However, these studies have still not clarified the cause of the reduced tumour suppressive effect of BATF2.…”
Section: Introductionmentioning
confidence: 90%